Music and youth culture in Latin America identity construction processes from New York to Buenos Aires - Vila, Pablo 1952- (Currents in Latin American and Iberian music, 2014)
The book examines the ways in which music is used to advance identity claims in several Latin American countries and among Latinos in the U.S. Individual chapters address the ways in which music provides people with both enjoyment and the tools they use to understand who they are in terms of nationality, region, race, ethnicity, class, gender, and migration status."